2018
DOI: 10.2134/jeq2018.01.0023
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Emissions from Subalpine Forest and Mountain Grassland Soils in Rocky Mountain National Park

Abstract: Atmospheric deposition of NH and NH contributes to eutrophication within sensitive subalpine ecosystems of Rocky Mountain National Park (RMNP) in the United States. However, little is known about the local contribution of NH from soils within the park. Thus, the goal of this study was to quantify and compare NH emissions from intact soil cores sampled from a subalpine grassland and forest within RMNP. Cores were collected at 2-wk intervals from 20 June 2011 to 12 Sept. 2011 and transferred to a laboratory cham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…forest. 33 The EC measurements were conducted from July to August in 2015 and from June to August in 2016. Soil NH 3 emissions from the grassland and the forest areas have been measured with detailed soil information.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…forest. 33 The EC measurements were conducted from July to August in 2015 and from June to August in 2016. Soil NH 3 emissions from the grassland and the forest areas have been measured with detailed soil information.…”
Section: Methodsmentioning
confidence: 99%
“…Soil NH 3 emissions from the grassland and the forest areas have been measured with detailed soil information. 33 N r deposition at the site has been measured annually (3.65 kg N ha −1 yr −1 in 2009), which includes wet N deposition and dry deposition estimates of nitric acid (HNO 3 ), NH 3 , particulate ammonium (NH 4 + ), and particulate nitrate. Dry NH 3 deposition was estimated by multiplying NH 3 concentrations by scaled HNO 3 deposition velocity.…”
Section: Methodsmentioning
confidence: 99%
“…This assumes all extracted [NH 4 + ] represents the amount found in soil pore water that can volatilize into the atmosphere. Recent chamber studies of soil, either of core samples [15] or overtop the intact soil [38,39], overcome this limitation by measuring the NH 3 emission directly. However, enclosure experiments, such as chambers, have difficulty in recreating the turbulent mixing that regulates the transfer velocity between the soil and atmosphere under ambient conditions, which is critical for fluxes that are driven by a compensation point, such as for NH 3 .…”
Section: Challenges Of Measuring Nh 3 In Ecosystem Compartmentsmentioning
confidence: 99%
“…The correlation they observed with air temperature led to the assumption the plant canopy was solely responsible for increased NH 3 concentrations in the NH 3 -poor air. More than two decades later, a study examined the soil contribution of NH 3 emissions to the atmosphere within the Colorado Front Range [15]. Based on chamber measurements of extracted soil cores, Stratton et al reported an average emission flux of 0.21 ± 0.03 mg NH 3 -N m −2 d −1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation